Assessing comfort level with pediatric skin specimens among dermatopathologists and pediatric pathologists: A national cross‐sectional survey. (14th March 2021) - Enos, Tyler; Hughes, Connor; Kelley, Shannon; Mir, Adnan; Rakheja, Dinesh; Vandergriff, Travis
Abstract: Background: Cutaneous histopathologic diagnoses in children often differ from those in adults. Depending on practice setting, these specimens may be evaluated by dermatopathologists or pediatric pathologists. We sought to determine whether comfort level with pediatric dermatopathology is associated with prior training, pediatric dermatopathology exposure during fellowship, career duration, or specimen subtype. Methods: We surveyed dermatopathologists and pediatric pathologists practicing in the United States. Training and practice variables were evaluated by multivariable regression for association with comfort level. Results: Of the 156 respondents, 72% were dermatopathologists (response rate 11.6%) and 28% were pediatric pathologists (response rate 9.3%). Dermatopathologists reported higher comfort overall ( P  < .001); this was also true for inflammatory dermatoses and melanocytic neoplasms ( P  < .001). Thirty‐four percent and 75% of dermatopathologists and pediatric pathologists, respectively, reported lower comfort with pediatric skin specimens than their usual cases. Pediatric pathologists were 28% more likely to refer these cases to colleagues. Among dermatopathologists, dermatology‐trained were more comfortable than pathology‐trained colleagues interpreting inflammatory dermatoses ( P  < .001). Conclusions: Pathologists' comfort with pediatric dermatopathology varied significantly based upon prior training, career duration, and specimen subtype. These results suggest opportunities for improving education in this domain.